2016
DOI: 10.1016/j.bbr.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The PDE4 inhibitor roflumilast improves memory in rodents at non-emetic doses

Abstract: Enhancement of central availability of the second messenger cAMP is a promising approach to improve cognitive function. Pharmacological inhibition of phosphodiesterase type 4 (PDE4), a group of cAMP hydrolyzing enzymes in the brain, has been shown to improve cognitive performances in rodents and monkeys. However, inhibition of PDE4 is generally associated with severe emetic side-effects. Roflumilast, an FDA-approved PDE4 inhibitor for treatment of chronic obstructive pulmonary disease (COPD), is yielding only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 62 publications
2
92
0
Order By: Relevance
“…Although roflumilast is considered as a non-selective inhibitor for all PDE4 isoforms, in particular the PDE4B and PDE4D isoforms in the hippocampus [109], it might be suggested that it has differences in intrinsic properties still. This could also be concluded from our previous preclinical work comparing pro-cognitive and emetic-like effects in mice between roflumilast and the similarly non-selective PDE4 inhibitor rolipram [107]. Rolipram induced emetic-like effects at pro-cognitive doses, while roflumilast had a significant difference between the high doses inducing emesis-like behavior and low doses improving cognition.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Although roflumilast is considered as a non-selective inhibitor for all PDE4 isoforms, in particular the PDE4B and PDE4D isoforms in the hippocampus [109], it might be suggested that it has differences in intrinsic properties still. This could also be concluded from our previous preclinical work comparing pro-cognitive and emetic-like effects in mice between roflumilast and the similarly non-selective PDE4 inhibitor rolipram [107]. Rolipram induced emetic-like effects at pro-cognitive doses, while roflumilast had a significant difference between the high doses inducing emesis-like behavior and low doses improving cognition.…”
Section: Resultsmentioning
confidence: 50%
“…Of note, PDE inhibitors have narrow dose-response ranges in preclinical animal research. They mostly have only one to two optimum doses when using a log scale [107,108]. This makes it difficult to titrate the effective dose for human studies.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo , roflumilast mitigates the tobacco smoke-induced lung inflammation, pulmonary vascular remodeling and hypertension [18]. Roflumilast is the brain penetrant; its concentration in the brain increases in a dose-dependent manner [19, 20]. It is effective on hypertension-induced impairment of learning and >memory [19] and the cognitive deficit in rodents at non-emetic doses [20].…”
Section: Introductionmentioning
confidence: 99%
“…The most common side-effects seen in association with the use of riociguat are headache, dizziness, dyspepsia, peripheral oedema, nausea, diarrhoea and vomiting. Based on our experience with roflumilast in animals (Vanmierlo et al 2016) and humans (Heckman et al 2018; Van Duinen et al 2018), the formula of Reagan-Shaw et al (2008) was used to calculate the appropriate dose. Therefore, we suggested that a dose of 0.5 and 1.0 mg was sufficient to improve memory performance.…”
Section: Methodsmentioning
confidence: 99%